Corporate governance and voluntary disclosure in Malaysia - Mohd Ghazali, Nazli Anum (Inderscience Publishers, 2010)
The purpose of this study is to examine the relationship between corporate governance and voluntary disclosure. The expectation is that with the introduction of the Malaysian Code on Corporate Governance in 2000, companies would be more aware of the need to have good governance and that good governance would lead to enhanced transparency. Regression analysis was performed on data collected from annual reports for years 2001 and 2006. Consistent with expectation, the extent of voluntary disclosure has increased from 2001 to 2006. The increase was statistically significant at the 5% level. However contrary to expectation, none of the corporate governance variables recommended in the Code was statistically significant.